Economic Evaluation of Broilers Performance under Coloured Light Emitting Diodes and Incandescent Supplemental Lighting - Kumar, Suresh; Gupta, Ravi Kant; Singh, Yashpal; Sharma , Amit; Kashyap, Neeraj (International Journal of Livestock Research, 2019)
The present study was designed to evaluate the broiler birds’ performance using light emitting diodes (LEDs) and incandescent light. For this purpose 240 straight run commercial Cobb broiler chicks were procured and distributed in four different light treatment groups i.e. T1; white (650nm), T2; green (565nm) and T3; blue (430nm) light LED (3 Watt each) and incandescent light bulbs (60 Watt each) as control (Tc) in 12 pens (4x3 factorial design). The data on growth performance indicated that final body weight, body weight gain and feed intake were higher in LED light treatment groups over the incandescent light bulbs. However, numerically lower FCR, higher PER and EER was found in LED light treatment groups. The data on economic benefits indicated that benefit cost ratio of LED light treatment groups (T1, T2 and T3) was higher (1:1.18, 1:1.18 and 1: 1.15) as compared to incandescent bulb treatment (TC) i.e. 1:1.05. From the study, it can be concluded that birds under LED light treatment showed improved growth performance by increasing the overall body weight gain, reducing the FCR and by better benefit cost ratio.